John Martin papers - Martin, John, 1837-1884.
Chiefly correspondence of Martin during his Civil War service as a soldier and musician in the 116th New York Infantry Regiment. Discusses regimental operations in Louisiana especially during the siege of Port Hudson in 1863; Baltimore and Frederick, Md.; New York state; Camp Sheridan in Winchester, Va.; and Washington D.C. Includes a pro-Union speech from 1861, a newspaper clipping concerning death of Martin, and genealogical material.
Union soldier.
Collection material in English.
Keywords: Martin family; United States. -- Army. -- New York Infantry Regiment, 116th (1862-1865); Baltimore (Md.) -- History; Camp Sheridan (Va.) -- History; Frederick (Md.) -- History; Louisiana -- History -- Civil War, 1861-1865.; Maryland -- History -- Civil War, 1861-1865.; New York (State) -- History -- Civil War, 1861-1865.; Port Hudson (La.) -- History -- Siege, 1863.; Virginia -- History -- Civil War, 1861-1865.; Washington (D.C.) -- History -- Civil War, 1861-1865.; Winchester (Va.) -- History; United States -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Songs and music; Soldiers